La comunicación científica en Instagram destinada al público infantil: los casos de @muyinteresantejunior y @revistacucu - Mireya Rocío CARBALLEDA CAMACHO,Dr. Francisco Javier RUIZ DEL OLMO (Fonseca, Journal of Communication, 2023)
Science communication for children is an essential issue in the context of advanced technological societies, not only in order to understand the nature of scientific advances but also to increase interest in science from a very early age and, in short, to raise the scientific culture of citizens. The main objective of this research is to analyse and describe the different strategies for communicating science to children and young audiences, which are carried out on social media by publica-tions focused on these audiences